Torpedo maculopathy. Issue 3 (12th October 2009) - Golchet, Pamela R; Jampol, Lee M; Mathura, Jeevan R; Daily, Mark J
Abstract : Aim: To describe the fluorescein angiographic, fundus autofluorescence and optical coherence tomography (OCT) findings in patients with a unique unilateral lesion of the temporal macula previously named torpedo maculopathy. Method: This study was a retrospective, observational case series. The medical records of 13 patients, age 1–68 years, seen between 1982 and 2009 were reviewed. Patients were evaluated for lesion features and course on follow-up, visual acuity, fluorescein angiography, visual-field defects, fundus autofluorescence and OCT findings. Results: In all 13 patients, the lesion was flat, torpedo-shaped and solitary, and involved the temporal macula. The hypopigmented lesion had well-defined margins and a characteristic leading edge which pointed towards the centre of the macula. Fluorescein angiography revealed transmission hyperfluorescence of the lesion. OCT indicated a thin abnormal retinal pigment epithelium signal, and Humphrey Visual Field testing revealed a corresponding blind spot. Fundus autofluorescence performed on one patient was dark in the affected area. Conclusion: Torpedo maculopathy is an apparently congenital hypopigmented torpedo-shaped lesion of the temporal macula. Although it may result in a corresponding visual-field defect, these non-foveal lesions do not affect central visual acuity.